PELAKSANAAN TATA CARA MAKAN ALA PRASMANAN BAGI TUNANETRA X DI KOTA PAYAKUMBUH - Ranti Sapta Rianti (Jurnal Penelitian Pendidikan Khusus, 2014)
Abstract:   This study discusses a Blind X who often visit a party with a buffet-style system. The purpose of this study is to describe how the shape of imple- menting the procedure for buffet-style meals made blind when visiting party. This type of research is descriptive qualitative study approach case, which is an approach with a focus on the case in detailed and intensive, and uses real data on verbal and qualifications are theoretical. Data collection techniques used are observation, interviews, and supported by photo documentation. While defending their subject is a visually impairedBased on the results of research carried out shows that a visually impaired X experiencing difficulty in eating buffet-style layout, because the barriers experienced. X visually impaired want to shape the implementation of the code of how to eat independently, from procedures take cutlery etiquette to take drinks. It is not performing well for the visually impaired difficult to adapt to the surroundings, cause a variety of visually impaired experienced constraints in dining etiquette, and not could do with a good dining etiquette. With all the difficulties experienced visually impaired is striving to overcome difficulties with a variety of disabilities, one disabled can be done visually impaired that is actively asking and asking for help to people in the area, so that it can perform the activity independently and good eating. Kata Kunci: Tunanetra; Tata Cara Makan ala Prasmanan